2020
DOI: 10.1021/acsomega.0c05194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcination Temperature on the Activation Performance and Reaction Mechanism of Ce–Mn–Ru/TiO2 Catalysts for Selective Catalytic Reduction of NO with NH3

Abstract: In this study, anatase TiO 2 -supported cerium, manganese, and ruthenium mixed oxides (CeO x −MnO x −RuO x / TiO 2 ; CMRT catalysts) were synthesized at different calcination temperatures via conventional impregnation methods and used for selective catalytic reduction (SCR) of NO x with NH 3 . The effect of calcination temperature on the structure, redox properties, activation performance, surface-acidity properties, and catalytic properties of the CMRT catalysts was investigated. The results show that the CMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 63 publications
(151 reference statements)
0
8
0
Order By: Relevance
“…The crystallite size of THNF increased from 15.67, 21.45 to 30.03 nm as the calcination temperature increased. Higher calcination temperature had reduced the activation energy, thus promoting the crystal growth rate [ 27 ]. It was commonly known that the surface area is inversely proportional to the crystallite size because there is a greater proportion of crystals and more area to occupy [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The crystallite size of THNF increased from 15.67, 21.45 to 30.03 nm as the calcination temperature increased. Higher calcination temperature had reduced the activation energy, thus promoting the crystal growth rate [ 27 ]. It was commonly known that the surface area is inversely proportional to the crystallite size because there is a greater proportion of crystals and more area to occupy [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In view of that Ce 4+ in octahedral anti-prismatic configuration shares structural similarity with Mn 3+ in distorted octahedral configuration, and the radius of Ce 4+ is larger than that of Mn 3+ , the incorporation of Ce 4+ into MnO 2 would induce the distortion of the crystal lattice and create more defects, which modulates the surface acidity, oxygen mobility, and redox property of catalysts. , Moreover, the formation of uniform Ce–Mn solid solution favors the dispersion of active sites on the surface and the enhancement of porosity . In the light of the advantages of Ce–Mn composite oxides, their catalytic performance has been explored in various applications, such as high-temperature gasifier effluent desulfurization, adsorption of mercury, and catalytic reduction of NO with NH 3 . It is found that the catalytic performance of Ce–Mn composite oxides was generally related to the valence state of Mn, Ce, and the distribution of oxygen species, which could be tuned by regulating the composition ratios or constructing a core–shell structure. , However, the synergistic effect of Ce–Mn on the catalytic activity and selectivity of the H 2 S-SCO reaction is yet to be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…It is gradually applied in flue gas denitration. [16] In recent years, fly ash combined with other substances as a denitration carrier has been studied by scholars in recent years. When fly ash is used as a carrier for denitration without modification, the denitration efficiency is relatively low, mainly due to the lack of effective active components.…”
Section: Introductionmentioning
confidence: 99%
“…Fly ash has a wide range of sources and has certain physical properties. It is gradually applied in flue gas denitration [16] . In recent years, fly ash combined with other substances as a denitration carrier has been studied by scholars in recent years.…”
Section: Introductionmentioning
confidence: 99%